An experimental study simulating the dissolution of gypsum rock. Issue 4 (July 2018) - Hong, Dongdong; Fan, Ming; Yu, Lingjie; Cao, Jian
The dissolution of gypsum rock is of significance to study because it affects the formation of hydrocarbon reservoirs, cap rocks and evaporite deposits. However, the characteristics and mechanism of the dissolution process remain unclear. Here, we present data from experiments performed to address this issue. The experiments simulate various geological conditions, including different diagenetic stages of burial under different fluid types. The diagenetic stages include: 30°C and 0.3 MPa for the epidiagenetic stage; 60°C and 13 MPa for the early diagenetic stage; 100°C and 27 MPa for the middle diagenetic stage; and 150°C and 43 MPa for the late diagenetic stage. The different fluid types include pure water representing continental water, seawater, 0.3 wt.% CO2 solution representing meteoric water, and a 0.2 wt.% acetic acid solution representing organic fluid. We also carried out the experiments on limestones and dolomites, because these rocks also occur in saline water sedimentary systems with gypsum rocks. Experimental results show that lithology, fluid type and temperature–pressure conditions can all affect dissolution. In terms of lithology, gypsum rocks dissolve more easily than limestones and dolomites. Fluid type has little effect on the dissolution of gypsum rock, and gypsum is soluble in all four types of fluids. In contrast, limestones and dolomites are almost insoluble in pure water and seawater, but show clear dissolution in CO2 and acetic acid solutions. The data indicate that gypsum rock has a dissolution peak close to the early diagenetic stage. In contrast, limestones and dolomites have dissolution peaks in the CO2 solution at the early–middle diagenetic stage, and do not show a peak in the acetic acid solution under surficial temperature–pressure conditions. The dissolution rates of limestone and dolomite show different trends with increasing temperature and pressure: limestone dissolution rates decline whereas dolomite dissolution rates increase. Therefore, we infer that the physicochemical properties of a rock are important drivers of dissolution.